Role of nutritional deficiency in the development of autism spectrum disorders - Oommen, Anitha; Alomar, Reem S. (International Journal of Research in Medical Sciences, 2020)
Autism spectrum disorders (ASD) are characterized by behavioural abnormalities and impaired communication skills. Both genetic and environmental factors have been attributed as causative factors. It has been reported that there are alterations in the organization of functional networks in brain as well as in the balance between structural and functional net-works in brain in children and adolescents with ASD when compared to normal children. Various studies have shown that lower levels of micronutrients like magnesium, selenium, Vitamin A, Vitamin D and Vitamin E, Folic acid and iron are found in children with ASD. This narrative review was undertaken to highlight the role of nutritional deficiency in the development of ASD in children relevant literature was collected from Google scholar, Pubmed, Cross Ref and Scopus. This review also takes into consideration how nutritional deficiency during pregnancy, infancy and childhood can have a role in the development of ASD in children.